Accelerated Decomposition of Potassium Permanganate in Ferrocenium Ion as Ferrocenium-Doped Manganese(IV) Oxide for Selective Oxidation of Alcohols - Chumkaeo, Peerapong; Poonsawat, Thinnaphat; Yunita, Isti; Temnuch, Natcha; Meechai, Titiya; Kumpan, Nuttapong; Khamthip, Achjana; Chuaitammakit, Laksamee Chaicharoenwimolkul; Chairam, Sanoe; Somsook, Ekasith (Synlett, 2022)
Ferrocenium-doped manganese(IV) oxide (Fc+/MnO2) was synthesized through accelerated decomposition of KMnO4 in the presence of ferrocenium ion (Fc+) generated by concentrated sulfuric acid. The corresponding catalysts enabled highly efficient oxidation of alcohols with aldehyde or ketone.
Keywords: decomposition; ferrocenium ion; manganese(IV) oxide; aerobic oxidation; alcohols